Adjunct Therapy With Glycyrrhiza Glabra Rapidly Improves Outcome in Depression—A Pilot Study to Support 11-Beta-Hydroxysteroid Dehydrogenase Type 2 Inhibition as a New Target - Murck, Harald; Lehr, Lisa; Hahn, Johannes; Braunisch, Matthias C.; Jezova, Daniela; Zavorotnyy, Maxim (Frontiers in Psychiatry, 2020)
Mineralocorticoid-receptor (MR) dysfunction as expressed by low systolic blood pressure and a high salivary aldosterone/cortisol ratio, predict less favorable antidepressant treatment outcome. Inhibition of peripheral 11-beta-hydroxysteroid-dehydrogenase type 2 (11betaHSD2) reverses these markers. We therefore tested the hypothesis that the 11betaHSD2 inhibitor glycyrrhizin affects treatment outcome via this mechanism. We administered Glycyrrhiza glabra (GG) extract containing 7-8 % of glycyrrhizin at a dose of 2 x 700 mg daily adjunct to standard antidepressants in hospitalized patients with major depression. These subjects were compared in an open label fashion with patients, who did not receive GG. Assessments were done at baseline and approximately 2 weeks after. Twelve subjects were treated with GG and compared to 55 subjects with treatment as usual (TAU). At week 2, the Hamilton-Depression Rating Scale (HAMD-21) change from baseline as well as the CGI-S change showed a significant time x treatment interaction (p < 0.03), indicating a possible therapeutic benefit of GG. Clinical benefit seems to be more pronounced in subjects with lower systolic blood pressure and significantly correlated with reduced sleep duration in the GG group. Our preliminary data show that treatment with the 11betaHSD2 inhibitor glycyrrhizin may possess a beneficial effect on antidepressant response, which may be specific to a defined depression subtype.